Medium-term financial planning: An answer to community budget crises? - Gerhard Stahl (Intereconomics, 1989)
In June 1988 the Council, the European Parliament and the Commission concluded an “Interinstitutional Agreement on Budgetary Discipline and Improvement of the Budgetary Procedure”. A key element of the agreement is a commitment to medium-term financial planning for the Community for the period up to 1992. Can this agreement put the Community budgetary procedure on a new footing and ensure that the decisions taken at the Brussels summit on agricultural reform and budgetary discipline can be implemented?
Keywords: 330; European Community